Characterization of an aged alkali-activated slag roof tile after 30 years of exposure to Northern Scandinavian weather. Issue 40 (12th September 2022) - Luukkonen, Tero; Yliniemi, Juho; Walkley, Brant; Geddes, Daniel; Griffith, Ben; Hanna, John V.; Provis, John L.; Kinnunen, Paivo; Illikainen, Mirja
Abstract : The phase assemblage and nanostructural characterization results reported here further elucidate the long-term changes occurring in alkali activated blast furnace slag binders. Abstract : Alkali-activated materials (AAMs) have been known as an alternative cementitious binder in construction for more than 120 years. Several buildings utilizing AAMs were realized in Europe in the 1950s–1980s. During the last 30 years, the interest towards AAMs has been reinvigorated due to the potentially lower CO2 footprint in comparison to Portland cement. However, one often-raised issue with AAMs is the lack of long-term studies concerning durability in realistic conditions. In the present study, we examined a roof tile, which was prepared from alkali-activated blast furnace slag mortar and exposed to harsh Northern Scandinavian weather conditions in Turku, Finland, for approximately 30 years. Characterization of this roof tile provides unique and crucial information about the changes occurring during AAM lifetime. The results obtained with a suite of analytical techniques indicate that the roof tile had maintained excellent durability properties with little sign of structural disintegration in real-life living lab conditions, and thus provide in part assurance that AAM-based binders can be safely adopted in harsh climates. The phase assemblage and nanostructural characterization results reported here further elucidate the long-term changes occurring in AAMs and provide reference points for accelerated durability tests and thermodynamic modelling.